2020
DOI: 10.3390/antiox9111123
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Compounds of Edible Fruits with Their Anti-Aging Properties: A Comprehensive Review to Prolong Human Life

Abstract: Aging is a complicated biological process in which functional and structural alterations in a living organism take place over time. Reactive oxygen species is one of the main factors responsible for aging and is associated with several chronic pathologies. The relationship between aging and diet is quite interesting and has attained worldwide attention. Healthy food, in addition to dietary antioxidants, are required to delay the process of aging and improve the quality of life. Many healthy foods such as fruit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
77
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 151 publications
(96 citation statements)
references
References 238 publications
0
77
0
1
Order By: Relevance
“…In fact, many dietary antioxidants are highly efficient in contrasting oxidative damage, and act as free radical scavengers. Huge amount of vegetables, fruits and berries are a rich source of natural antioxidants, such as anthocyanins, biophenols, vitamins, and other phytochemicals, which are actively involved in slowing down the ageing process [ 3 ]. Recently, several phytochemical complexes with antioxidant function have been identified as potential therapeutic agents to prevent/treat neurodegeneration disorders [ 4 , 5 , 6 , 7 ].…”
mentioning
confidence: 99%
“…In fact, many dietary antioxidants are highly efficient in contrasting oxidative damage, and act as free radical scavengers. Huge amount of vegetables, fruits and berries are a rich source of natural antioxidants, such as anthocyanins, biophenols, vitamins, and other phytochemicals, which are actively involved in slowing down the ageing process [ 3 ]. Recently, several phytochemical complexes with antioxidant function have been identified as potential therapeutic agents to prevent/treat neurodegeneration disorders [ 4 , 5 , 6 , 7 ].…”
mentioning
confidence: 99%
“…Besides macro and micronutrients, also the protective effect of bioactives such as polyphenols against oxidative stress has been largely investigated [ 18 ]. A number of studies have shown the capacity of these compounds to neutralize the harmful effect of reactive oxygen species as well as to disrupt their propagation [ 53 , 54 ]. Furthermore, several studies have reported their ability to increase the activity of numerous antioxidant enzymes (e.g., catalase, superoxide dismutase, glutathione peroxidase) and to upregulate nuclear factor erythroid-related factor and antioxidant-responsive elements, crucial for the modulation of oxidative stress and thus DNA damage [ 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…The effectiveness of these phytochemicals used in treating jaundice and other diseases has been seen in their biological activities, such as antimicrobial, antibacterial, antitumor, antiviral, or antioxidant activity. The oxidative stress of free radicals is directly associated with the presence of pathogenic organisms or due to disease-causing mechanisms of different ailments like cancer, diabetes, and inflammatory diseases [117].…”
Section: Plant Name Phytochemical Constituent Data Sourcementioning
confidence: 99%